2007
DOI: 10.1167/iovs.07-0427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Memantine on Neuroretinal Function and Retinal Vascular Changes of Streptozotocin-Induced Diabetic Rats

Abstract: These results indicate that MEM could be useful for the treatment of ocular diseases, including diabetic retinopathy with neurodegeneration, elevated vitreoretinal VEGF protein levels, and increased BRB breakdown. In addition to the neuroprotective effect of this compound, MEM can reduce vascular changes seen in diabetic retinas. These data are the first to identify the vasculoprotective effect of MEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 52 publications
7
86
0
Order By: Relevance
“…The number of retinal ganglion cells were counted on each photograph automatically using a software system (CPAS software, Daheng software Ltd, Beijing, China). 7 About 500-700 cells per eye were counted. The photographs covered a retinal area of about 0.25 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of retinal ganglion cells were counted on each photograph automatically using a software system (CPAS software, Daheng software Ltd, Beijing, China). 7 About 500-700 cells per eye were counted. The photographs covered a retinal area of about 0.25 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It has, therefore, been desirable to develop treatment strategies by which the retina and optic nerve can be protected from degeneration by helping the retinal cells to survive even under difficult conditions. Recent studies have reported that substances such as ciliary neurotrophic factor, [3][4][5] brain-derived growth factor, 6 memantine, 7,8 and Ginkgo biloba may have a stabilizing or protecting effect on retinal cells in experimental conditions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Particularly for Ginkgo biloba, potential antioxidant functions have been discussed to be helpful for impaired retinal cells such as Mü ller cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chronic memantine treatment decreased elevated vitreoretinal VEGF protein levels and blood-retinal barrier breakdown in diabetic rats [226]. Recently, Smith et al demonstrated that the s receptor 1 ligand(+)-pentazocine treatment conferred significant neuro protection, reduced evidence of oxidative stress and preserved retinal architecture in diabetic mice [227].…”
Section: Neuroprotectionmentioning
confidence: 99%
“…If one considers just the protection of RGCs, a plethora of approaches can be collected from the literature. For example, anti-inflammatory drugs such as nonsteroidal cyclooxygenase inhibitor nepafenac Krady et al, 2005;Vincent and Mohr, 2007); several salicylates (Zhang et al, 2007); the glutamate NMDA receptor antagonist, memantine (Kusari et al, 2007); cannabidiol (CBD) (El-Remessy et al, 2006); NGF (Hammes et al, 1995b); IGF-1 (Seigel et al, 2006); aldose reductase inhibitors (Asnaghi et al, 2003); erythropoietin (EPO) To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter SPi. It is not allowed to publish this proof online or in print.…”
Section: Experimental Approaches To the Treatment Of Diabetic Retinopmentioning
confidence: 99%
“…Memantine significantly improved amplitudes of ERG a and b waves. Another possible mechanism of the neuroprotective effect of memantine in the retinas of STZ-induced diabetic rats could be the inhibition of retinal type 3 serotonin and nicotinic Ach receptors, although elevated serotonin and acetylcholine levels have not been demonstrated in diabetic retina (Kusari et al, 2007). 4.6.3.6 Nepafenac p1335 Nepafenac is a prodrug of amfenac, a nonsteroidal anti-inflammatory drug that inhibits COX-1 and COX-2 and the synthesis of proinflammatory prostaglandins (Kapin et al, 2003).…”
Section: Calpain Inhibitorsmentioning
confidence: 99%